Hypertension Control and Cardiovascular Risk Profiles in Patients with Established Coronary Artery Disease: A Single-Centre Study - Handayani, Ahmad; Safar, Farha Sonia; Guhtama, Muhammad Ary (Universitas Ahmad Dahlan, 2026)
Coronary artery disease (CAD) remains a leading cause of global morbidity and mortality, driven by interconnected risk factors such as hypertension, diabetes mellitus, smoking, obesity, and dyslipidemia. Effective management of these factors is essential in secondary prevention. This study aimed to compare the level of hypertension control with other cardiometabolic risk factors among CAD patients. Using a cross-sectional design, 40 CAD patients with multiple risk factors at Mitra Medika Amplas Hospital were assessed for hypertension control, smoking status, blood glucose regulation, achievement of ideal body weight, and dyslipidemia management based on clinical measurements and questionnaire data. Data were analyzed using descriptive statistics. Associations between risk factors and their level of control were assessed using the Chi-square test, with Fisher’s exact test applied when expected cell counts were small. Hypertension emerged as the most well-controlled risk factor, whereas blood glucose, body weight, and especially dyslipidemia showed poor levels of control. The study also found that an increasing number of coexisting risk factors correlated with progressively lower control of each individual factor. These findings underscore the need for more comprehensive, structured, and multidisciplinary risk-factor management to improve the effectiveness of secondary prevention in CAD patients.